Isoflurane Postconditioning Upregulates Phosphorylated Connexin 43 in the Middle Cerebral Artery Occlusion Model and Is Probably Associated with the TGF-β1/Smad2/3 Signaling Pathway. - Yin, Jiangwen; Liu, Xuejiao; Wang, Ruixue; Ge, Mingyue; Xie, Liping; Zhai, Jingwen; Dai, Zhigang; Li, Yan; Wang, Sheng (BioMed Research International, 2020)
Aim. Connexin 43 (Cx43) has been identified to be important for cerebral ischemia/reperfusion (I/R) injury as well as protection from it. This study was aimed at investigating the relationship between phosphorylated Cx43 (p-Cx43), transforming growth factor-β1 (TGF-β1)/Smad2/3 signaling pathway, and isoflurane postconditioning (ISPOC), which has effects on brain injury in rats with cerebral ischemia/reperfusion (I/R) injury. Methods. The middle cerebral artery occlusion (MCAO) model was induced in 96 male Sprague-Dawley rats, weighing 250-300 g. The rats were randomized into 12 groups, namely, sham, middle cerebral artery occlusion (MCAO)/I/R, I/R+1.5% ISPOC, I/R+LY2157299 (blocker of TGF-β1), I/R+LY2157299+1.5% ISPOC, I/R+Ro318220 (inhibitor of p-Cx43), I/R+Ro318220+1.5% ISPOC, I/R+18β-GA (activator of p-Cx43), I/R+18β-GA+1.5% ISPOC, I/R+1.5%ISPOC+LY2157299+Ro318220, dimethyl sulfoxide (DMSO), and 1.5% ISPOC+DMSO. The protective effect of 1.5% ISPOC was tested by neurological deficit scoring and 2,3,5-triphenyl tetrazolium chloride staining (TTC staining). The terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) method and hematoxylin-eosin (HE) staining were used to observe apoptosis of CA1 cells in the hippocampus. The function of protein synthesis in neurons was tested by Nissl staining. Expression levels of TGF-β1, Smad2/3, phosphorylated Smad2/3 (p-Smad2/3), Cx43, and phosphorylated Cx43 (p-Cx43) were measured by Western blot, immunofluorescence (IF), and quantitative real-time polymerase chain reaction (qRT-PCR). Results. Neurological deficit scores, brain infarct volume, and damaged neurons in the I/R group significantly increased compared to those in the sham group (P < 0.05). However, in the ISPOC group, damage of the brain was significantly ameliorated (P < 0.05). qRT-PCR showed more p-Cx43 mRNA expression in the hippocampal tissue of the ISPOC group than of the I/R group (P < 0.05). Western blot and immunofluorescence results showed similar changes in p-Cx43 protein levels of both groups. The expression levels of related proteins (TGF-β1 and p-Smad2/3) both increased in the ISPOC group (P < 0.05), whereas total Smad2/3 and total Cx43 expression did not change in all groups. However, when a TGF-β1 inhibitor (LY2157299) was applied, expression levels of p-Cx43 significantly decreased as well as neuronal density (P < 0.05). By contrast, expression levels of TGF-β1 did not change significantly after the application of a p-Cx43 inhibitor (Ro318220) or the p-Cx43 activator 18β-GA (P > 0.05). Conclusion. Isoflurane postconditioning (ISPOC) may alleviate cerebral I/R injury through upregulating the expression of p-Cx43, and the TGF-β1/Smad2/3 signaling pathway may be involved in the process.